Start with why : how great leaders inspire everyone to take action - Sinek, Simon (2011)
Why are some people and organizations more innovative, more influential, and more profitable than others? Why do some command greater loyalty? In studying the leaders who've had the greatest influence in the world, Simon Sinek discovered that they all think, act, and communicate in the exact same way-and it's the complete opposite of what everyone else does. People like Martin Luther King Jr., Steve Jobs, and the Wright Brothers might have little in common, but they all started with why. Drawing on a wide range of real-life stories, Sinek weaves together a clear vision of what it truly takes to lead and inspire.
Preface: The power of why -- Introduction: Why start with why? -- A world that doesn't start with why: Assume you know ; Carrots and sticks -- An alternative perspective: The golden circle ; This is not opinion, this is biology ; Clarity, discipline, and consistency -- Leaders need a following: The emergence of trust ; How a tipping point tips -- How to rally those who believe: Start with why, but know how ; Know why. Know how. Then what? ; Communication is not about speaking, it's about listening -- The biggest challenge is success: When why goes fuzzy ; Split happens -- Discover why: The origins of a why ; The new competition -- Afterword: Be a part of this movement, share your vision of the world.
"This paperback edition with a new preface and new afterword published 2011"--Title page verso.
Includes bibliographical references (pages 234-240) and index.
Keywords: Leadership; Leadership; Interpersonal Relations